UJI TEKNIS ALAT TANAM JAGUNG (Zea mays L.) TIPE TP CSM 15 DENGAN MENGGUNAKAN TRAKTOR TANGAN SEBAGAI ALAT PENARIK1) - Idhansyah .; Ruland A Rantung; Daniel P. M Ludong (Universitas Sam Ratulangi, 2018)
ABSTRACT This study aims to test technically the corn seeds planter (Zea mays L.) type TP CSM (Corn seeding machine) 15 using the hand tractor as a pulling device on the plot of the land 30 m x 10 m. The test results of TP CSM 15 corn seeds planter in 30 m x 10 m plot of the land on 3 field tests with soil treatment got the average effective field capacity of 0,30 ha/hour, the average theoretical field efficiency of 0,47 ha/hour, and the average field efficiency of 64,20 %. The average distance between planting rows is 73,2 cm and the average distance in row planting is 28,4 cm. The number of seeds per planting hole 1 – 3 with an average of 1 seed per planting hole and an average planting depth of 5.5 cm. The percentage of seeds which grew successfully by an average of 75,74% and the percentage of seeds which unsuccessfully to grow by an average of 24,26%. Keywords : TP CSM 15, Hand Tractor, Field Efficiency.